Validation of an in-house lattice Boltzmann solver for a multiphase flow application - Figueroa-González, A.; Oliveira, J.; Teschner, Tom-Robin; Könözsy, László Z.; Moulitsas, Irene; Jenkins, Karl W. (International Center for Numerical Methods in Engineering (CIMNE), 2018)
This paper focuses on a validation study in conjunction with an in-house Lattice Boltzmann Method (LBM) based code for a multiphase flow application. The LBM technique takes into account one partial differential equation for each fluid component of multiphase flows to describe the evolution of a particle distribution function. In the present work, a numerical study has been carried out to investigate the behaviour of a heavy and elliptic bubble immersed in a lighter fluid which oscillates until the equilibrium state is reached. The benchmark problem of an oscillating bubble has been implemented, validated and investigated in conjunction with the Colour Gradient Model (CGM).
Keywords: Validation and Verification; Multiphase Flows; Lattice Boltzmann Method